Effects of saccadic eye movements on postural control stabilization - Rodrigues, Sérgio Tosi [UNESP]; Aguiar, Stefane Aline; Polastri, Paula Fávaro [UNESP]; Godoi, Daniela; Moraes, Renato [UNESP]; Barela, José Angelo [UNESP] (FapUNIFESP (SciELO), 2013)
Several structures of the central nervous system share involvement in both ocular and postural control, but the visual mechanisms in postural control are still unclear. There are discrepant evidences on whether saccades would improve or deteriorate stabilization of posture. The purpose of this study was to determine the influence of saccadic eye movements on postural control while standing in different basis of support. Twelve young adults stood upright in wide and narrow stances while performing fixation and saccades of low and high frequencies. Body sway was attenuated during saccades. Trunk anterior-posterior sway and trunk total displacement decreased during saccades compared to fixation; higher sway mean frequency in anterior-posterior direction during saccades was observed. Body sway was reduced in wide compared to narrow stance during high frequency saccades. These results indicate that eye movement improves postural stabilization and this effect is stronger in combination of wide stance-high frequency gaze condition.
Keywords: Eye movements; Posture; Saccades